Lenalidomide and vorinostat maintenance after autologous transplant in multiple myeloma. (8th June 2015) - Sborov, Douglas W.; Benson, Don M.; Williams, Nita; Huang, Ying; Bowers, Mindy A.; Humphries, Kristina; Efebera, Yvonne; Devine, Steven; Hofmeister, Craig C.
Summary Single‐agent post‐autologous transplant maintenance therapy with lenalidomide is standard of care for patients with multiple myeloma. The tolerability and effectiveness of combination post‐transplant maintenance therapy is unknown, so we investigated lenalidomide and vorinostat (suberoylanilide hydroxamic acid) in this setting, hypothesizing that the regimen would be well tolerated and associated with an improved post‐transplant response. This trial followed a standard 3 × 3 dose escalation phase 1 design. Vorinostat was administered beginning day +90 post‐haematopoietic stem cell transplantation for days 1–7 and 15–21, and lenalidomide was started at 10 mg days 1–21, both on a 28‐d cycle. The primary endpoint was maximum tolerated dose and dose limiting toxicities were assessed during the first cycle. Treatment was well tolerated in 16 enrolled patients. During Cycle 1, the most common toxicities included cytopenias, gastrointestinal complaints and fatigue. Seven patients improved their transplant response after starting combination therapy. The median follow‐up was 38·4 months, and the median progression‐free survival and overall survival have yet to be reached. This oral post‐transplant maintenance regimen was well tolerated. This is the first trial to publish results on the use of a histone deacetylase inhibitor in the maintenance setting, and it provides rationale for the ongoing randomized trial in maintenance (ISRCTN 49407852). Trial Registration: NCT00729118